Prognostic implications of biventricular uptake of bone tracers at planar scintigraphy in transthyretin cardiac amyloidosis. (3rd October 2022) - Porcari, A; Pagura, L; Canepa, M; Biagini, E; Cappelli, F; Tini, G; Dore, F; Longhi, S; Sciagra', R; Fontana, M; Gillmore, J; Rapezzi, C; et al.
Abstract: Background: The prognostic role of bone tracer uptake in transthyretin cardiac amyloidosis (ATTR-CA) is controversial. A further characterization of cardiac retention measured by Perugini scale with differentiation between biventricular (BiV) and isolated left ventricle (LV) uptake has never been attempted previously. Purpose: The study investigated the potential prognostic significance of BiV uptake in ATTR-CA. Methods: In this multicentre, observational study, we analysed data of ATTR-CA patients who underwent bone tracer scintigraphy with acquisition of both planar and single photon emission computed tomography (SPECT) imaging. Cardiac uptake was defined according to the Perugini visual scale. Planar BiV uptake was defined according to right ventricle (RV) uptake: 0= absent, 1= < bone, 2= equal to bone, and 3= > bone and confirmed by SPECT imaging. The primary outcome was a composite of cardiac death or hospitalization for heart failure. The secondary outcome was all-cause mortality. Results: All 124 ATTR-CA patients enrolled had LV and RV free wall uptake on SPECT images. Of them, 93 (75%) had BiV uptake visible on planar scintigraphy. BiV uptake was found in 14%, 70%, and 92% of Perugini grade 1, 2 and 3 respectively. Compared to those with isolated LV uptake, patients with BiV uptake were older (81 vs 77 years, p=0.006) and more frequently in NYHA≥3 (32% vs 10%, p=0.018). During a median follow-up of 21 months, BiV uptake was associated with a greater occurrence of the primary outcome compared to isolated LV uptake (40% vs 19%, p=0.021), whereas the Perugini scale was not (p=0.2) (Figure 1). At multivariable analysis, NYHA class ≥3 (hazard ratio [HR] 8.1, p=0.007), eGFR <60 ml/min (HR 2.1, p=0.025) and higher degree of RV uptake (HR 1.69, p=0.007) emerged as independent prognostic parameters. In an external cohort of 463 ATTR-CA patients with a median follow-up of 30 months, planar BiV uptake was independently associated with all-cause mortality, with an incremental risk in higher grades of RV uptake (p<0.001) (Figure 1). Conclusions: The presence of BiV uptake at planar scintigraphy identified ATTR-CA patients with worse cardiovascular and global outcomes (Figure 2), potentially serving as a novel prognostic marker. Funding Acknowledgement: Type of funding sources: None.